PHP India: the e-commerce dilemma. Issue 1 (12th January 2022) - Kamath, Renuka; Pawar, Nilendra Singh
Abstract : Learning outcomes: Through the analysis of the case, the students will be able to: 1. appreciate the dynamics in a multi-channel environment especially in the relatively new ecommerce space in India; 2. understand the decision-making process and the impact on various stakeholders in adopting a new ecommerce sales channel; and 3. evaluate financial implications of channel profitability and its implication on the decision. Case overview/synopsis: Philadelphia Home Products (PHP) India was facing a sales slowdown and was looking at a foray into the e-commerce channel, as an answer for business growth. The decision was not an easy one, as it had implications on existing channel partnerships and the organization. Channel choice decisions had acquired a new dimension with the proliferation of ecommerce platforms and changing online consumer buying habits. It was January 2015 and Nandini Devgan, CEO of PHP India was with her experienced team, who clearly had differing points of view. She needed to put the organization back on a growth trajectory, but how does she balance the various differing views put forth by her team? Was entering the ecommerce channel the best option? Complexity academic level: This case is designed for use at the postgraduate level in courses, such as sales management, channel management, e-commerce and strategic marketing courses, as well as in executive management programs. The case is relevant from the context of channel management of a Consumer-Packaged Goods company in India, where e-commerce is nascent yet growing. It gives students a practical hands-on decision-making situation, where there are complexities of quantitative and qualitative nature. It triggers a discussion where the chief executive officer (CEO) and her team are facing growth and profitability issues, and have to take a decision on whether or not to adopt the e-commerce channel while managing the existing channels. Supplementary materials: Teaching note is available for educators only. Subject code: CSS 8: Marketing.